The determination of the stability constants of mixed ligand complex of Fe(III), ethylenediamine tetraacetic acid (EDTA) and 5-sulphosalicylicacid (SSA) by potentiometric method - (:unkn) unknown (My University, 1998)
In the present study, the suitable conditions for the formation of Fe(III), Ethylenediamine tetraacetic acid (EDTA) and 5-Sulphosalicylic acid (SSA) mixed complex were investigated and the stability constant of this triple complex was determined by using Irwing-Rossotti potentiometric procedure. The protonation and acid constants were found I = 0.11 and pK = 12.9 at 25°C respectively (1). In addition, the conditional formation constants of complexes formed were calculated depending on the pH (2). The relative abundances of several species derived from this mixed complex were investigated by using these conditional formation constants. The protonation constants of SSA and EDTA, used as ligands (Table 1) and the stability constants of the binary complexes (Table 2) were taken from the literature (3).
Keywords: 5-Sulphosalicylic acid; Ethylenediamine tetraacetic acid; Fe(III) complexes; Mixed complex; Stability constants